Sonic Hybridity, Cultural Continuity, and Musical Identity: Gamelan Pesel in Contemporary Bali - I Wayan Suharta; I Gde Made Indra Sadguna; Yung-Hsin Wang (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
This article examines gamelan pesel, an innovative hybrid ensemble created by I Wayan Arik Wirawan that fuses the sonic and material characteristics of semar pegulingan and selonding. Through qualitative methods, including organological analysis, participant observation, interviews, and digital ethnography, this research explores how gamelan pesel embodies “sonic hybridity,” a process through which Balinese musicians negotiate between tradition and innovation. The findings reveal that gamelan pesel’s creative design integrates bronze and iron instruments to generate a new timbral spectrum, while its unique tuning system and intercontextual performances across ritual, social-cultural, and digital media articulate a dynamic redefinition of Balinese musical identity. Rather than signaling a rupture with tradition, the ensemble exemplifies progressive traditionalism, where renewal sustains continuity. This study contributes to ethnomusicological and cultural discourse by illustrating how new ensembles can nurture cultural continuity through experimentation and adaptation.